Development of internal developer platform for software development lifecycle optimization - Olgaç, Ahmet Vehbi; Zileli, Erkan; Karadaş, Gökhan; Ulus, Ceren; Akay, M. Fatih (Edelweiss Applied Science and Technology, 2025)
New technologies are constantly developing, processes are progressing rapidly, and many items that need to be followed and managed are emerging. In this context, the need for new approaches to increase efficiency, collaboration, and innovation for software development and technology teams is constantly increasing. The Internal Developer Platform (IDP) is a solution to meet these needs. This study aims to develop an IDP that supports development activities and application needs at Trendyol. A platform has been developed that provides a unified and integrated environment, empowering developers, accelerating development cycles, and ensuring the delivery of high-quality software products. Kubernetes, KubeVela, and GitLab have been used to develop the IDP. Golang and JavaScript have been used as software development languages, and Couchbase and Elasticsearch have been used as databases. As a result, with the developed IDP, more than 3,000 applications within Trendyol have been integrated into the system. The results highlight that the entire deployment process of an application is now completely under the control of developers, eliminating the need to wait for other teams to perform manual operations. The findings of this study may endorse saving time spent on manual operational processes, allowing developers to focus directly on the development process and maximize their individual productivity.